Prenatal Progestin Exposure-Mediated Oxytocin Suppression Contributes to Social Deficits in Mouse Offspring - Huang, Saijun; Zeng, Jiaying; Sun, Ruoyu; Yu, Hong; Zhang, Haimou; Su, Xi; Yao, Paul (Frontiers in Endocrinology, 2022)
Epidemiological studies have shown that maternal hormone exposure is associated with autism spectrum disorders (ASD). The hormone oxytocin (OXT) is a central nervous neuropeptide that plays an important role in social behaviors as well as ASD etiology, although the detailed mechanism remains largely unknown. In this study, we aim to investigate the potential role and contribution of OXT to prenatal progestin exposure-mediated mouse offspring. Our in vitro study in the hypothalamic neurons that isolated from paraventricular nuclei area of mice showed that transient progestin exposure causes persistent epigenetic changes on the OXT promoter, resulting in dissociation of estrogen receptor β (ERβ) and retinoic acid-related orphan receptor α (RORA) from the OXT promoter with subsequent persistent OXT suppression. Our in vivo study showed that prenatal exposure of medroxyprogesterone acetate (MPA) triggers social deficits in mouse offspring; prenatal OXT deficiency in OXT knockdown mouse partly mimics, while postnatal ERβ expression or postnatal OXT peptide injection partly ameliorates, prenatal MPA exposure-mediated social deficits, which include impaired social interaction and social abilities. On the other hand, OXT had no effect on prenatal MPA exposure-mediated anxiety-like behaviors. We conclude that prenatal MPA exposure-mediated oxytocin suppression contributes to social deficits in mouse offspring.